2020
DOI: 10.3389/fnhum.2019.00468
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reorganization of SMA Subregions After Stroke: A Subregional Level Resting-State Functional Connectivity Study

Abstract: Background and Purpose: The human supplementary motor area (SMA) contains two functional subregions of the SMA proper and preSMA; however, the reorganization patterns of the two SMA subregions after stroke remain uncertain. Meanwhile, a focal subcortical lesion may affect the overall functional reorganization of brain networks. We sought to identify the differential reorganization of the SMA subregions after subcortical stroke using the resting-state functional connectivity (rsFC) analysis. Methods: Resting-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In contrast, repetitive somatosensory and motor stimuli, and cognitive stimuli reflect increased resting-state functional connectivity (rsFC) in the brain network, which may be related to the aggregation of neurotransmitter receptors at synaptic terminals (Tung et al, 2013;Wei et al, 2014). Some studies have shown increased rsFC of the CMA with other motor-related cortical brain regions in stroke patients (Liu et al, 2020), which contradicts the results of the present study, but may indicate that the CMA and insula have different patterns from normal activity in processing movements related to pain sensation. The present study links the insula to the CMA is an attempt to explain its reduced connectivity with decreased motor function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, repetitive somatosensory and motor stimuli, and cognitive stimuli reflect increased resting-state functional connectivity (rsFC) in the brain network, which may be related to the aggregation of neurotransmitter receptors at synaptic terminals (Tung et al, 2013;Wei et al, 2014). Some studies have shown increased rsFC of the CMA with other motor-related cortical brain regions in stroke patients (Liu et al, 2020), which contradicts the results of the present study, but may indicate that the CMA and insula have different patterns from normal activity in processing movements related to pain sensation. The present study links the insula to the CMA is an attempt to explain its reduced connectivity with decreased motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, regions of the PreCG, as well as the PoCG, significantly positively correlated with FMA-UE scores. Previous studies of motor dysfunction in stroke described major changes in motor-related brain regions, including the primary motor cortex and SMA, and even rewired synaptic connections ( Kim et al, 2018 ; Liu et al, 2020 ). Our result reached a consistent conclusion with previous studies that exercise execution can mainly be attributed to the activation of motor-related brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Together these studies suggest that SMA might be able to compensate when there is damage to the motor execution network. Anatomically, this can be supported by the rich connections that SMA has with multiple parts of the motor system, such as the primary motor cortex ( Kim et al, 2010 ) and basal ganglia ( Liu et al, 2020 ). Functionally, the SMA has been shown to receive preparatory signals on the order of information from pre-SMA and to send driving signals to the motor regions that execute motor commands ( Bohland et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%